Avaliação do status taxonômico de uma linhagem de rãzinha-da- serrapilheira do complexo Adenomera simonstuarti das florestas de areia branca da Reserva de Desenvolvimento Sustentável do Rio Negro, Amazônia Central, Brasil - Martins, Bryan da Cunha (2023)
Through integrative taxonomy we describe a new species of foam-nesting frog of the genus Adenomera from white-sand forests of the Reserva do Desenvolvimento Sustentável Rio Negro, Central Amazonia, Brazil. Within the A. andreae Clade, the new species nest within A. simonstuarti complex as sister to the lineage A. simonstuarti 2 from Lower Juruá. The new species is assigned to the genus Adenomera by having smaller than 34.1 mm, lack of fringing and webbing between toes and the absence of spines in adult males' thumbs. It differs from other Adenomera Amazonian species by the combination of the following characters: absence of antebrachial tubercle; toe tips flattened or slightly flattened, with visible expansions; presence of nearly solid dark-colored stripe on underside of forearm; single-note call formed by 11–21 partly fused pulses; fundamental and dominant frequencies varying between 1,765–2,239 Hz and 3,448–4,349 Hz, respectively; call duration varying between 100–199 ms. Although we have sampled many permanent sampling modules in ombrophilous forests in Manaus region and in the Purus-Madeira interfluve in the last decade, the new species was only found in the white-sand forest from West Negro-Solimões Interfluve, which indicate that Adenomera sp. nov. might be an endemic or at least a specialist in this kind of environment in the Negro-Solimões interfluve.